A development of 500N thrust rocket motor using KNO3 carbon propellant [electronic resource] - Amir Aziz, author; Fakulti Kejuruteraan Mekanikal (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2008